(untitled) (Research, Society and Development, 2022)
With the advent of the Covid-19 pandemic, in 2020, there was a need to carry out the so-called "social isolation" as a measure to contain the spread of the virus. This caused changes in the children’s routine, which could significantly impact their health, due to factors such as increased sedentary lifestyle and poor diet, which are associated with weight gain and the development of health problems. Therefore, the objective was to evaluate the consequences of social isolation in the increase of excess weight in children in the school stage. Diagnostic data on the nutritional status of children aged 5 to 10 years were analyzed, between the years 2019 and 2021, from the five Brazilian regions, through reports from the Food and Nutrition Surveillance System (SISVAN) of the Ministry of Health. According to the results, there was an increase in weight in children over the years in all Brazilian regions, and the height-for-age indicator did not change significantly. The period of social isolation caused by the Covid-19 pandemic may have contributed to the increase in overweight and obesity in school children.